An Introduction to Compressible Flows with Applications : Quasi-One-Dimensional Approximation and General Formulation for Subsonic, Transonic and Supersonic Flows /: Quasi-One-Dimensional Approximation and General Formulation for Subsonic, Transonic and Supersonic Flows. (2019) - Pontes, José; Mangiavacchi, Norberto; Anjos, Gustavo R
No abstract available